Low nitrogen stress-induced transcriptome changes revealed the molecular response and tolerance characteristics in maintaining the C/N balance of sugar beet (Beta vulgaris L.) - Li, Jiajia; Liu, Xinyu; Xu, Lingqing; Li, Wangsheng; Yao, Qi; Yin, Xilong; Wang, Qiuhong; Tan, Wenbo; Xing, Wang; Liu, Dali (Frontiers in Plant Science, 2023)
Nitrogen (N) is an essential macronutrient for plants, acting as a common limiting factor for crop yield. The application of nitrogen fertilizer is related to the sustainable development of both crops and the environment. To further explore the molecular response of sugar beet under low nitrogen (LN) supply, transcriptome analysis was performed on the LN-tolerant germplasm ‘780016B/12 superior’. In total, 580 differentially expressed genes (DEGs) were identified in leaves, and 1075 DEGs were identified in roots (log2| FC |≥1; q value<0.05). Gene Ontology (GO), protein‒protein interaction (PPI) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses clarified the role and relationship of DEGs under LN stress. Most of the downregulated DEGs were closely related to ‘photosynthesis’ and the metabolism of ‘photosynthesis - antenna proteins’, ‘carbon’, ‘nitrogen’ and ‘glutathione’, while the upregulated DEGs were involved in flavonoid and phenylalanine biosynthesis. For example, GLUDB (glutamate dehydrogenase B) was identified as a key downregulated gene, linking carbon, nitrogen and glutamate metabolism. Thus, low nitrogen-tolerant sugar beet reduced energy expenditure mainly by reducing the synthesis of energy-consuming amino acids, which in turn improved tolerance to low nitrogen stress. The glutathione metabolism biosynthesis pathway was promoted to quench ROS and protect cells from oxidative damage. The upregulated expression of 4CL2 (4-coumarate-CoA ligase 2), CAD6 (probable cinnamyl alcohol dehydrogenase 6), BGLU (beta-glucosidase) and PER (peroxidase) enhanced phenylalanine metabolism by eliminating hydrogen peroxide and promoting lignin biosynthesis, which in turn maintained proteome homeostasis and improved plant tolerance to low nitrogen stress. DFRA (dihydroflavonol 4-reductase) in roots was negatively correlated with NIR (ferredoxin-nitrite reductase) in leaves (coefficient = -0.98, p < 0.05), suggesting that there may be corresponding remote regulation between ‘flavonoid biosynthesis’ and ‘nitrogen metabolism’ in roots and leaves. FBP (fructose-1,6-bisphosphatase) and PGK (phosphoglycerate kinase) were significantly positively correlated (p < 0.001) with Ci (intercellular CO2 concentration). The reliability and reproducibility of the RNA-Seq data were further confirmed by qRT‒PCR validation of 22 genes (R2 = 0.98). This study reveals possible pivotal genes and metabolic pathways for sugar beet adaptation to nitrogen-deficient environments.